TANGGUNG JAWAB NOTARIS DALAM SENGKETA PARA PIHAK TERKAIT AKTA PERJANJIAN PENGIKATAN JUAL BELI (PPJB) YANG DIBUATNYA - Aulia Gumilang Rosadi (JCH (Jurnal Cendekia Hukum), 2020)
Public Notary as an official appointed by the Government who has the authority (bevoegdheid) and responsibilities which, if reviewed comprehensively, could potentially be subjected to administrative, civil or criminal claims when a dispute related to the deed which is made by him/her. The main issues discussed in this study are; 1) How chosen for a notary and parties in the binding sales purchase agreement ? 2) How responsibility the parties upon an agreement in the agreement on binding sales of a bell Which is drawn up before the notary ? 3) How a form of responsibility the notary in dispute the parties related the binding sales purchase agreement made ? The research is a normative juridical research with statute approach. The data used are secondary data in the form of; primary, secondary and tertiary legal materials. The results shows that the notary is administratively, civil and criminally responsible for the deed and the process of forming the deed itself, so the notary needs to implement a policy based on regulations so that he/she with the deed he/she made and the parties can be protected by law.